RANCANG BANGUN SISTEM KONTROL POWER STEERING PADA TRAINER SISTEM KEMUDI SEBAGAI MEDIA PEMBELAJARAN PRAKTEK CHASSIS - Pradana, Enggal Putra; Ansori, Aris (Universitas Negeri Surabaya, 2021)
The control system trainer as a medium for students and lecturers to make communication and learning effective so that the teaching and learning process becomes more effective. There is still no instructional media trainer for learning in the chassis technology subject at the State University of Surabaya for the hydraulic power steering control system, which can easily be understood and studied by students, especially mechanical engineering. Therefore, the authors make learning media that discusses the workings of the power steering control system and can find out the pressure generated from the hydraulic power steering. R&D (Research and Development) method or experimental-based development design. With the aim of being able to determine the specifications of the main drive components that will be used in the design and build of a hydraulic power steering control system. The results of the analysis of the pressure test work show that the pressure generated from various speeds shows different results, so that it affects the weight of the steering system. For hydraulic power steering at low speed the steering will feel heavy but at high speed conditions the steering will feel light. The implication is that the pressure in the steering system is directly proportional to the speed of the vehicle. The results obtained from the power steering pressure when turning right with a speed of 700 rpm at 20 Psi, 1000 rpm at 30 Psi, 1300 rpm at 40 Psi and 1700 at 60 Psi. while when turning to the left, the results obtained at rpm 700 of 20 Psi, rpm 1000 of 30 Psi, rpm 1300 of 40 Psi and rpm 1700 of 50 Psi.